PASAL 284 KUHP PERSPEKTIF HUKUM ISLAM (JURNAL HUKUM SEHASEN, 2019)
There is a different point between Article 284 of the Criminal Code and Islamic law concerning Adultery, Conducting marital relations by adult men and adult women by liking, while both male adulterers and adulterous women are not bound by marital ties with other parties ( perpetrators of adultery) or for him not bound by article 29 BW, then the perpetrators can not be said to be adultery, while Islam does not distinguish girls or single, widowed or widower, where engaging in marital relations without going through marriage is committing adultery. Keywords: Article 284 of the Criminal Code and Islamic Law